Harga Diri dan Penerimaan Diri Remaja Akhir di Panti Asuhan Sonaf Maneka Kelurahan Lasiana Kota Kupang - Mathilda Primordiani Rinmalae; Tadeus A. L. Regaletha; Juliana Marlin Y Benu (Universitas Nusa Cendana, 2019)
Self-esteem is an individual's assessment of their own self, self worth, whether it’s positive or negative. The assessment is the result of individual interaction with their environment, the other people recognition and personal experiences. While self-acceptance is a positive attitude towards one's own characteristics, either being satisfied with their strength and recognize their limitations in living life. The purposeof this study was to determine the effect of self-esteem on self-acceptance of late adolescents at the Sonaf Maneka Orphanage, Lasiana Village, Kupang. This study used quantitative approach. This study used total population sampling technique with total were 48 adolescent aged from 15-20 years old. Data collection used self-esteem scale adapted from Resty (2015) and self-acceptance scale develop by researcher based onHurlock’s theory (Noviani, 2016). Hypothesis testing uses a simple linear regression test. The results of the study show that self-esteem have significant positive effect on self-acceptance with a value of p (0.000) <0.05. Therefore, it can be concluded that the self-esteem variable can predict the self-acceptance variable. Effective contribution of self-esteem variable to self-acceptance variable is 33.6%.